Minat Wirausaha, Konsep Diri dan Kreativitas - Rita Kusuma Eka Ananta; Djalali; Muhammad Farid (University of Merdeka Malang, 2014)
This research aimed to examine the relationship between self concept and creativity with students interest in entrepreneurship. The partisipants were class XII student SMKN 2 and 4 Madiun, totally 420 students. Date collection metod used scale interest in enterprenuer, self concept, CORE scale. Data analysis used was multiple regressions. Analytical result obtained by double regress F (59,840), p = 0,000 (p 0,01) which means that self concept and creativity have a significant relationship with interest in enterprenuership. The result of correlation analysis between self concept by showing interest in enterpreneurship with t (9,580), p = 0,000 (p 0.05) which means there was a very significant positive correlation between self concept and interest in enterprenuership.The result of correlation analysis between creativity and interrest entreprenuership showed t (2,012) with p = 0,046 (p 0.05) which means there was significant positive correlatioan between creativity and interest in enterprenuership.